Middle East Oil, Gas and Geosciences Show 2023
DOI: 10.2118/213633-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative and Independent Method for Formation Strengths and Facies Identification Using Real-Time Downhole Drilling Data, and its Application in Geosteering for Optimal Well Placement

Abstract: Understanding of rock strength, and its variability along the length of the well, is essential for building an efficient well trajectory during geosteering operations. Traditionally, drill cuttings, surface gas analysis, measurements while drilling (MWD) data and Logging While Drilling (LWD) measurements have been used to optimize trajectories. Rock mechanical properties, derived from petrophysical well logs are key to drilling, production and recovery potential of the well: However, in a vast majority of geos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…They found that MWD parameters showed significant changes in response to geological features, such as open joints or cavities, providing a method to correlate drilling parameters with rock mass structures. Prasad et al [20] presented an innovative method for real-time downhole drilling data to identify formation strengths and facies. This method utilizes MWD data to infer rock strength and variability along the wellbore.…”
Section: Introductionmentioning
confidence: 99%
“…They found that MWD parameters showed significant changes in response to geological features, such as open joints or cavities, providing a method to correlate drilling parameters with rock mass structures. Prasad et al [20] presented an innovative method for real-time downhole drilling data to identify formation strengths and facies. This method utilizes MWD data to infer rock strength and variability along the wellbore.…”
Section: Introductionmentioning
confidence: 99%